RICH IRRIGATION SYSTEM FLOURISHED AGRICULTURE AS GLEANED FROM EPIGRAPHS (Journal of Pharmaceutical Negative Results, 2022)
The agricultural prosperity of a country depends upon the sound irrigation system which it builds. Early civilization flourished on the river banks, where water was available in plenty. Inscriptions of the later Pallava Kings state that a separate committee called eri-variyam came into being to look after the tanks, lakes, etc. An inscription of Kampavarman from Uttiramerur reveals that the great people constituting the eri-variyam (the tank committee) had to spend a certain sum from the capital towards keeping the tanks in condition. Padikaval tax was collected by the local police authority to give protection to the cultivable land. Padikaval system became very popular since it had determined the political status of the Padikaval authorities. The Padikkaval authority was very popular in Tondaimandalam and it became immense in number from the heyday of the Cholas down to the decline of the Chola Empire.This paper mainly concentrated on various irrigation system and agriculture how to flourish in ancient times in detailed manner.